2017
DOI: 10.1177/0046958017734030
|View full text |Cite
|
Sign up to set email alerts
|

Asking About Pets Enhances Patient Communication and Care: A Pilot Study

Abstract: This research explored whether asking patients about their pets would enable better environmental/social history taking, and improve patient communication/care. Primary health care providers (PHPs) were surveyed about prevalence of patients living with pets, the health impact of pets, and influences on patient communication. Following an educational intervention, they committed to asking patients about their pets. A follow-up survey was conducted electronically. PHPs were recruited at a continuing medical educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Additionally, investigators used a previously developed educational brochure, including 25 references, which discussed zooeyia, zoonotic risk, and encouraged communication among all health-care providers of a pet owner's family (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, investigators used a previously developed educational brochure, including 25 references, which discussed zooeyia, zoonotic risk, and encouraged communication among all health-care providers of a pet owner's family (12).…”
Section: Methodsmentioning
confidence: 99%
“…In the second arm of the study, PHPs were recruited in 2 ways. At a conference of 6 area hospitals, investigators recruited PHPs who visited a booth featuring related work (12). Additional participants were recruited at continuing medical education events in the spring of 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot study surveying primary health care providers who had participated in an educational intervention about the use of a pet query revealed that asking patients about their companion animals strengthened the therapeutic alliance and improved communication between patients and care providers. In turn, clinically important information was shared by patients which affected their treatment plans (Hodgson, et al, 2017). These findings have implications for social work practice, particularly social worker-client interaction and building rapport in the relationship (Hoy-Gerlach & Wehman, 2017; Tedeschi, Fitchett, & Molidor, 2005).…”
Section: Human-animal Interaction In Social Workmentioning
confidence: 99%
“…Research from veterinary and family medicine with valuable implications for social work is found in a study by Hodgson, Darling, Freeman and Monavvari (2017). The authors suggest asking animal questions during intake assessments to facilitate rapport between care providers, including social workers, and clients in a nonthreatening manner.…”
Section: Human-animal Interaction In Social Workmentioning
confidence: 99%